IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF JIGSAW BERBANTUAN LEMBAR KERJA SISWA DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF PADA MATERI PERUBAHAN LINGKUNGAN DI SMA - Ika Eunike Br Sembiring; Putu Budi Adnyana; Ida Bagus Putu Arnyana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the profile of students' cognitive learning outcome improvement, to analyze differences in cognitive learning outcomes between students taught using the Jigsaw cooperative learning model assisted by contextual student worksheets (LKS) and students taught using the Jigsaw model without contextual worksheets, and to determine the magnitude of the effect of the treatment on environmental change material. This study used a quantitative approach with a quasi-experimental type and a Pretest-Posttest Nonequivalent Control Group Design. The population comprised all Grade X students of SMA Negeri 1 Banjar in the 2025/2026 academic year, totaling 256 students. The sample was determined through purposive sampling with an intact-group approach, namely class X8 as the experimental class and class X6 as the control class, each consisting of 34 students. Data were collected through multiple-choice cognitive learning outcome tests administered before and after treatment, then analyzed using N-Gain, prerequisite tests, Analysis of Covariance (ANCOVA), and effect size through Partial Eta Squared. Results showed that the mean N-Gain of the experimental class was 0.62, higher than the control class at 0.36, although both fell into the moderate category. The most notable improvement in the experimental class occurred in the evaluating (C5) and creating (C6) aspects. The ANCOVA results showed a significance (p) of 0.005 (<0.05), indicating a significant difference in cognitive learning outcomes between the two classes after controlling for pretest scores. A Partial Eta Squared value of 0.117 indicated a moderate effect. This study concludes that the Jigsaw cooperative learning model assisted by contextual worksheets is more effective in improving cognitive learning outcomes, particularly students' higher-order thinking skills.